A new record for guyana reveals the disjunct distribution of tragia cearensis pax & K. Hoffm. (euphorbiaceae) - Cordeiro, Wesley Patrício Freire de Sá (2020)
Tragia cearensis, which was known only from northeastern Brazil in caatinga (dryland) vegetation, has its distribution expanded after the discovery of its presence in the savanna of Guyana, providing the first evidence of a disjunct distribution between those dry areas among Tragia species. Tragia cearensis could be recognized by having long, capitate, glandular trichomes at the apex of the petiole, the absence of glandular trichomes on the inflorescences and apices of the branches, and verrucose seeds. A detailed description, additional taxonomic notes, illustrations, and a distribution map are presented.